Do trilingual individuals exhibit an advantage over bilinguals in executive function tasks? - Jianlin Chen; Ci Jiang; Fang Liu (Acta Psychologica, 2025)
The literature has sparked a debate concerning whether bilingual individuals surpass monolinguals in executive functions, a concept known as the bilingual advantage. This leads to the question of whether this purported bilingual advantage extends to those who are trilingual or multilingual. Consequently, this study seeks to explore whether Tibetan-Chinese-English trilinguals highly proficient in L2 Chinese and learning English as L3 demonstrate superior executive functions in comparison to Chinese-English bilinguals learning English as a foreign language. To measure three distinct executive function sub-components—inhibitory control, information updating, and mental set shifting—we developed the Stroop task, the N-back task, and the switching task. Surprisingly, our results revealed that bilinguals outperformed trilinguals across all three tasks, suggesting late sequential trilinguals in this specific context show no advantage over bilinguals. These findings not only contribute to the ongoing dialogue regarding the bilingual advantage but also provide valuable insights into cognitive enhancement within specific linguistic contexts.